Can carotid angioplasty stenting be better than endarterectomy or best medical treatment for patients with carotid stenosis?. (3rd October 2022) - Fernandes, R; Silva, J D; Ferreira, J M; Goncalves, L
Abstract: Background: Carotid stenosis is responsible for a considerable amount of strokes and related deaths. Carotid angioplasty stenting (CAS), endarterectomy (CEA) and best medical treatment (BMT) are important in preventing major cardiovascular (CV) events. Methods: We conducted a systematic review and meta-analysis, with randomized controlled trials (RCT), to compare CAS with CEA and BMT regarding the short and long-term major periprocedural and follow-up CV events (stroke, myocardial infarction, and death) in symptomatic and asymptomatic carotid stenosis. We searched for RCT published from 2008 to 2021 in databases such as Pubmed/MEDLINE, B-On, Embase, Clinical Trials from U.S. National Library of Medicine and International Clinical Trials Registry Platform, between July of 2018 and January of 2019, and in October of 2021. Results: Nine RCT were included, with a total of 9162 participants for CAS versus (vs) CEA, and 513 participants for CAS vs TMO. Compared with CEA, CAS is associated with periprocedural stroke and death in symptomatic patients (HR=1.65, 95% CI: 1.29–2.11, p=0.05, I 2 =62%), due to higher stroke events than deaths. That association does not occur in asymptomatic patients in which CAS is not associated with periprocedural stroke or death (CAS=8.55%, CEA=7.05%, p=0.09). During follow-up there were no significant differences between CAS and CEA in symptomatic patients regarding stroke (HR=1.51, 95% CI: 1.23–1.84, p=0.57, I 2 =0%) and death (HR=1.10, 95% CI: 0.93–1.30, p=0.69, I 2 =0%). Periprocedural myocardial infarction (MI) incidence is higher in CEA (CAS=1.1%; CEA=2.3%; p=0.03), without influence of symptomatic status. CAS is not inferior to CEA, in both symptomatic and asymptomatic patients with high surgery risk, as for periprocedural and one year CV major events (CAS=12.2%, CEA=20.1%, absolute difference = −7.9, 95% CI: −16.4–0.7, p=0.004). BMT had no significant findings vs CAS in asymptomatic patients (HR=3.5, 95% CI: 0.42–29.11, p=0.246). Conclusion: CAS is not inferior to CEA as for the periprocedural and one-year major CV events in patients with normal surgery risk. However, there is a higher risk of periprocedural stroke in CAS for symptomatic patients, and of periprocedural MI in CEA with no influence of symptomatic status. CAS seams to prevent middle and long-term ipsilateral stroke in symptomatic patients. BMT has yet to prove not to be inferior to CAS in asymptomatic patients. Funding Acknowledgement: Type of funding sources: None.